Penerapan Expressive Writing sebagai Media Regulasi Emosi pada Siswa Islamic Boarding School SMP Unismuh Makassar - Pertiwi Nurani; Novianti Putri, Rukiana (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service activity was carried out at the Islamic Boarding School, SMP Unismuh Makassar, with a focus on improving students' emotional regulation through expressive writing techniques. The main problem faced by students is difficulty in managing and regulating emotions, which can potentially lead to mental health disorders, such as anxiety and stress. Through expressive writing-based training, students are taught to recognize, manage, and express their emotions in a healthy way. Expressive writing is expected to help students overcome emotional problems in a more positive way, reduce stress, and increase self-acceptance. This training was attended by 18 students with emotional regulation problems out of a total of 40 students at the Islamic Boarding School, SMP Unismuh Makassar. The activities included an introduction to types of emotions, emotional management exercises, and expressive writing as a means of emotional regulation. Evaluation results showed a significant increase in students' ability to identify and manage their emotions, with a decrease in stress symptoms and an increase in emotional well-being. This activity makes an important contribution to improving the quality of student mental health in the boarding school environment and is expected to be implemented more widely in other educational institutions.